2001
DOI: 10.1007/bf02988237
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Tc-99m MIBI SPECT in predicting multidrug resistance gene expression levels in non-small cell lung cancer—a preliminary report

Abstract: In this study we investigated whether Tc-99m hexakis 2-methoxy isobutyl isonitnile (Tc-99m MIBI) single-photon emission computed tomography (SPECT) has a correlation with the multidrug resistance (MDRI) and multidrug resistance-associated protein (MRP1) gene expression levels in non-small cell lung cancer (NSCLC). Fifteen patients with NSCLC were studied. SPECT images were obtained 15 (early) and 120 (delayed) min after injection of Tc-99m MIBI. We chose only one transverse section and set the region of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The in vivo results showed a lower retention of 64 Cu-ATSM and -PTSM in ArKO mice, despite a fatty liver indicating that although lipophilicity may favor initial penetration of the radiotracers, it is not sufficient to cause retention (29). Interestingly, ArKO liver retention and expression values were intermediate between wild-type and ArkO liver tumor, similar to the inverse relationship of 99m Tc-MIBI retention and MDR1 expression that has been noted in several cancers (5,6,10,(30)(31)(32)(33). Whether such an inverse relationship exists with 64 Cu-ATSM and -PTSM retention is unknown but could be the subject of future clinical studies.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The in vivo results showed a lower retention of 64 Cu-ATSM and -PTSM in ArKO mice, despite a fatty liver indicating that although lipophilicity may favor initial penetration of the radiotracers, it is not sufficient to cause retention (29). Interestingly, ArKO liver retention and expression values were intermediate between wild-type and ArkO liver tumor, similar to the inverse relationship of 99m Tc-MIBI retention and MDR1 expression that has been noted in several cancers (5,6,10,(30)(31)(32)(33). Whether such an inverse relationship exists with 64 Cu-ATSM and -PTSM retention is unknown but could be the subject of future clinical studies.…”
Section: Discussionsupporting
confidence: 54%
“…The most widely known imaging agent that is an MDR1 substrate is the lipophilic cationic radiopharmaceutical 99m Tc-hexakis-2-methoxyisobutylisonitrile ( 99m Tc-MIBI) (4). In general, studies have shown that tumor cells with high MDR1 expression show lower accumulation and faster washout of the tracer than do their parental cells with lower MDR1 expression (5)(6)(7)(8)(9)(10). A few studies have found decreased tumor or tumor cell retention of 99m Tc-MIBI in the presence of lower oxygen tension (7)(8)(9).…”
mentioning
confidence: 99%
“…This result is consistent with the previous data that 99m Tc-MIBI can predict the response to chemotherapy in various malignant tumors since MDR-1 drug resistant protein may be involved in transportation of 99m Tc-MIBI from the tumor cells. [1][2][3] The authors need to perform further experiments to determine whether the levels of MDR-1 expression really correlate with chemoresistance in meningioma cells. If they can clarify this point in the future, the information in this manuscript may be useful for considering chemotherapeutic approaches for patients with inoperable meningioma.…”
Section: Commentarymentioning
confidence: 99%
“…16) Technetium-99m sestamibi ( 99m Tc-MIBI), a lipophilic radiopharmaceutical, was developed as an alternative to 201 Tl for myocardial perfusion imaging, and is known to be taken up by various types of tumors including brain tumors. 2,3,23,25,37,38) 99m Tc-MIBI SPECT is clinically useful for distinguishing between high-grade and low-grade gliomas. 3,23,25,38) The uptake of 99m Tc-MIBI depends on the distribution of regional blood flow and on mitochondrial oxidation capacity, which is an indicator of cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 80% of lung cancer is attributed to non‐small cell lung cancer (NSCLC), with chemotherapy being the standard of care for NSCLC patients [2,3]. However, the overall response rate of NSCLC patients is only 30–50%, even with the best regimens [4,5], and these poor response rates lead to failed treatment in lung cancer.…”
Section: Introductionmentioning
confidence: 99%